COMPETITIVENESS OF TRANSPORT COMPANIES IN THE OPINION OF STUDENTS - Ginavičienė, Jurgita; Sprogytė, Indrė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The paper presents the results of a quantitative research study carried out with 280 transport logistics students in Lithuania. The research focused on the students’ opinion about the competitive advantage of Lithuanian transport companies. During their professional training, they filled out an electronic demographic data form online and evaluated the importance and attainability of the offered values on a 5-point Likert scale. The results revealed that when increasing the competitiveness of transport companies, the main attention should be paid to the customer - consumers, and their needs must be taken into account.